2015
DOI: 10.5114/wo.2015.54084
|View full text |Cite
|
Sign up to set email alerts
|

Dietary habits of lung cancer patients from the Lower Silesia region of Poland

Abstract: Aim of the studyAssessment of lung cancer patients’ dietary habits before treatment enable medical staff to provide more individual, precise and complex care to patients, taking into consideration their nutritional status. The aim of this study was, therefore, to evaluate dietary habits related to lung cancer risk of lung cancer patients in comparison with controls from the Lower Silesia region of Poland.Material and methodsAssessments of dietary habits, based on a validated questionnaire related to lung cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The changes in energy and nutrients intake are especially visible when we take into account separated cycles of cytotoxic chemotherapy [ 12 ]. Usually, the changes in energy intake are directly related to body weight changes [ 19 ]. Especially, as pointed out Grosvenor et al .…”
Section: Discussionmentioning
confidence: 99%
“…The changes in energy and nutrients intake are especially visible when we take into account separated cycles of cytotoxic chemotherapy [ 12 ]. Usually, the changes in energy intake are directly related to body weight changes [ 19 ]. Especially, as pointed out Grosvenor et al .…”
Section: Discussionmentioning
confidence: 99%
“…The main risk factors of lung cancer are cigarette smoking, occupational and genetic factors, as well as exposure to carcinogenic substances present in the air [ 2 , 3 ]. Dietary habits may, to some extent, modify the risk of its development [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…We were able to identify three well documented case control studies [77,81,82], and two studies with scant data [74,83]. Xu and Cai [82] and Zhong et al [77] found a decrease in lung cancer by GT in Chinese patients.…”
Section: Case-control Studiesmentioning
confidence: 99%